Experimental study of flow boiling heat transfer, frictional pressure drop, and exergy destruction of R513A in microfin tubes - Vidhyarthi, Neeraj Kumar; Deb, Sandipan; Gajghate, Sameer Sheshrao; Muhamad, Mat Noor; Pal, Sagnik; Das, Ajoy Kumar (Springer Science and Business Media Deutschland GmbH, 2025)
This research examines the heat transfer coefficient (HTC), frictional pressure drop (FPD), and exergy destruction characteristics of R513A during flow boiling in a microfin tube under varying conditions to assess the thermodynamic performance and efficiency. Experiments were conducted at heat fluxes (HF) of 6, 18, and 30 kW·m−2, mass fluxes (MF) of 75, 175, and 275 kg·m−2·s−1, and saturation temperatures (12 °C and 22 °C). The results demonstrate that HTC rises significantly with HF and MF, with approximately a 30% increase observed at the highest fluxes, attributed to intensified nucleate and convective boiling processes. Additionally, FPD is shown to increase by about 50% as MF rises, reflecting greater frictional resistance from liquid-vapor interactions at higher flow rates. Exergy destruction (ED) analysis indicates a 20% reduction in ED at elevated MF values, suggesting that increased flow rates enhance thermodynamic efficiency by reducing irreversibilities. The experimental data align well with established HTC and FPD correlations, with 94% and 92% of predicted values, respectively, falling within 10% of the experimental measurements. Exergy efficiency reaches its peak at intermediate vapor qualities, approximately 15% higher than at lower or higher qualities, highlighting an optimal balance between thermal and pressure drop losses. These findings underscore the potential of R513A in microfin tubes for energy-efficient applications in refrigeration and heat pumps, where optimized HF and MF can enhance HTC and minimize exergy losses, contributing to overall system performance improvements.